CASE STUDY: EDUCATION AND IMPLEMENTATION OF FEEDING RULES TO IMPROVE CHILDREN'S APPETITE AND MOTHERS' FEEDING BEHAVIORS FOR CHILDREN WITH STUNTING - Narantika, Dhea; Purnamasari, Meivita Dewi; Nani, Desiyani (International Journal of Biomedical Nursing Review, 2026)
Introduction: Stunting is a condition of short or very short stature based on the Length/Height-for-Age index. Feeding is a crucial part of life for infants and children under three (toddlers), and most parent-child interactions occur during feedings. Long-term feeding difficulties can lead to growth failure and delays in growth and development. One way to address feeding difficulties is through the implementation of feeding rules. Purpose: This case study aims to determine the effect of education and the application of feeding rules on child patients with stunting. Methods: This research is a qualitative study with a descriptive case study approach, compiled from nursing care reports using the nursing process. Based on the implementation of Evidence-Based Nursing (EBN) in nursing practice, the case study uses an activity flow based on Polit and Beck (2012). The instrument used in the study was a questionnaire. Discussion: The results of observations for 3 consecutive days after being given education showed that mothers were able to apply feeding rules with an increase in questionnaire results related to knowledge and application of feeding rules. Conclusion: There was an increase in children's appetite and mothers' behavior after being given education on feeding rules and implementing feeding rules.